Gates of Paradise : a Blue Bloods novel - De la Cruz, Melissa, 1971- (De la Cruz, Melissa, 1971- Blue Bloods novel, 2013)
"In the final installment of the Blue Bloods series, the young vampires of Manhattan must make terrible sacrifices in order to triumph over Lucifer and the Silver Bloods"--